Pengaruh Kompleksitas Perusahaan, Ukuran Perusahaan, Reputasi KAP dan Opini Audit terhadap Audit Delay - Nurul Sulistiyani; Artila Sayyidina Fasya (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research aims to evaluate the influence of company complexity, company size, KAP reputation, and audit opinion on audit delays in transportation sector service companies listed on the Indonesia Stock Exchange from 2018 to 2020. The background of this research is based on the importance of timeliness in submitting reports finance to maintain the trust of investors and other stakeholders. The research method used was purposive sampling with a sample of 66 companies which were analyzed using multiple regression using SPSS version 26 software. The research results showed that company complexity, company size and KAP reputation did not have a significant influence on audit delay, while audit opinion showed an influence. which is significant. The conclusions of this research indicate that although factors such as complexity and company size are often considered to influence audit delay, in the context of transportation sector companies, only audit opinion shows a significant correlation. This shows the need for companies to focus more on the quality of financial reports and transparency to reduce audit delays. These findings are expected to provide insight for companies, auditors and regulators in efforts to increase the efficiency of the audit process and the timeliness of financial reporting.